The woodland gang and the dinosaur bones - Schultz, Irene (Kalookan City : Addison-Wesley, 1991)
A gang of orphans and their housekeeper help Dr. Justin search an Arizona canyon for fossilized dinosaur remains, despite sabotage and theft caused by greedy miners.
Keywords: Orphans - Fiction; Dinosaurs - Fiction; Paleontology - Fiction; Mystery and detective stories